DEVELOPMENT OF PROJECT BASED WORKSHEETS ON THE MAKING OF FACIAL TONERS FROM CITRUS AURANTIFOLIA PEEL - Reza Iga Sahara; Neneng Windayani; Imelda Helsy (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to describe the preparation of project-based worksheets on the manufacture of facial toner from lime peel distillate (Citrus aurantifolia) and to analyze the results of the validity test of the Worksheet format on making facial toner from lime peel distillate (C. aurantifolia). The method used is Design. Based Research (DBR), with three stages 1) Analysis 2) Design 3) Development. The instrument used was a validation test questionnaire using the correlation technique. The results of the project-based worksheet validation test are declared valid with an average value of rcount of 0.85 which is included in the high validity category, thus the worksheet can be used to help the learning process on cosmeseutical material.